Analisis Elemen Ekuitas Merek RCTI dalam Persaingan Industri Televisi Swasta di Indonesia: Studi Kasus pada Empat Perguruan Tinggi Swasta Terkemuka di Jakarta - Masruroh Masruroh; Awin Indranto (Bina Nusantara University, 2008)
Article measured the element of RCTI brand equity consisting of brand awareness, brand association that formed brand image, perceived quality, and brand loyalty. The used research method was descriptive, this research desribe 400 student perception from four private universities in Jakarta on the RCTI brand equity in last 2005. The used sampling method was probability sampling using proportionate stratified random sampling technique. The brand awarness research result shows that RCTI brand is in the first level on top of mind level with 50,25% of the respondent. For the brand association, there are three associations that formed brand image of RCTI, which are RCTI Oke, Indonesian Idol, and Seputar Indonesia.